A RANDOMIZED DOUBLE-BLIND PLACEBO-CONTROL PILOT STUDY OF EPLERENONE FOR THE TREATMENT OF CENTRAL SEROUS CHORIORETINOPATHY (ECSELSIOR). Issue 5 (May 2018) - Rahimy, Ehsan; Pitcher, John D.; Hsu, Jason; Adam, Murtaza K.; Shahlaee, Abtin; Samara, Wasim A.; Vander, James F.; Kaiser, Richard S.; Chiang, Allen; Spirn, Marc J.; Fineman, Mitchell S.
Abstract : Purpose: To evaluate the safety and effects of oral eplerenone in chronic central serous chorioretinopathy. Methods: Prospective, randomized, double-blind, placebo-control study at a tertiary referral academic private practice. For a diagnosis of chronic central serous chorioretinopathy, patients must have had at least 3 months clinical follow-up demonstrating persistent symptoms, subfoveal fluid on spectral-domain optical coherence tomography, and <50% reduction in fluid thickness. Patients were randomized 2:1 (treatment:placebo) to receive eplerenone (25 mg daily for 1 week, then up to 50 mg daily for 8 weeks) or placebo once daily. Results: Fifteen patients completed the study. Ten patients (15 eyes) were randomized into the eplerenone treatment arm, while the remaining 5 patients (6 eyes) received placebo. After 9 weeks of eplerenone therapy, mean logarithm of the minimal angle of resolution visual acuity improved from 0.394 (Snellen equivalent: 20/50) to 0.330 (20/43, P = 0.04). In the placebo group, the mean logarithm of the minimal angle of resolution visual acuity slightly decreased from 0.313 (20/41) to 0.342 (20/44) during the same period ( P = 0.21). With respect to anatomic changes, mean maximal subretinal fluid height in the eplerenone group improved from 139.3 μ m at baseline to 51.8 μ m ( P = 0.02), mean subfoveal fluid height improved from 121.4 μ m to 29.4 μ m ( P = 0.01), and mean central subfield thickness improved from 366.2 μ m to 283.7 μ m ( P = 0.02). In comparison with the placebo group, mean maximal subretinal fluid height worsened from 135.9 μ m to 172.3 μ m ( P = 0.32), mean subfoveal fluid height worsened from 92.1 μ m to 134.0 μ m ( P = 0.54), and mean central subfield thickness worsened from 345.0 μ m to 380.0 μ m ( P = 0.37). No patients in either group experienced serious adverse events to result in treatment discontinuation. Conclusion: These findings suggest that oral eplerenone therapy is safe and potentially effective in the treatment of chronic central serous chorioretinopathy with persistent subretinal fluid. Abstract : This study was a prospective, double-blind, placebo-controlled evaluation of oral eplerenone for the treatment of chronic central serous chorioretinopathy. The results demonstrated improved visual acuity measurements as well as anatomic outcomes, as shown by reductions in mean maximal subretinal fluid height, subfoveal fluid height, and central subfield thickness.